EFL Teachers´ Research and Mainstream TESOL: Ships Passing in the Night? La investigación de profesores de inglés y la línea dominante en TESOL: ¿Barcos que pasan en la noche? - Isobel Rainey de Díaz (Profile: Issues in Teachers' Professional Development)
This article describes and analyses the concerns of EFL secondary school teachers who do, or would like to be doing, research into their own classroom practices. The study attempts to show that, despite claims to the contrary, these concerns are still not being accounted for in mainstream TESOL. Even though EFL teachers may have been given voice within their national contexts, that voice is neither being heard nor acted upon in the dominant TESOL community. It is suggested, therefore, that until EFL teachers from non-mainstream TESOL contexts not only benefit from but also contribute to that body of knowledge which forms the bedrock of TESOL, and from which many reforms derive, this profession will continue to be hegemonic and not truly representative of a global TESOL reality. Se describen y analizan las áreas de investigación que interesan a aquellos profesores de inglés, nivel secundario, que hacen o quieren hacer investigación en sus propios salones de clase. Aunque en la literatura se sostiene que hoy en día se toman en cuenta los intereses de dichos profesores, este estudio intenta demostrar que éste no es el caso. Aunque dentro de contextos nacionales se ha venido cediendo 'voz' a los profesores, la comunidad dominante de TESOL no ha parecido prestarle importancia. Por lo tanto, se sugiere reflexionar sobre el siguiente hecho: mientras los profesores de inglés de contextos no-dominantes no saquen provecho, ni contribuyan a los conocimientos que forman la base de TESOL, de los cuales se derivan muchas reformas, esta profesión seguirá siendo hegemónica.